Campur Kode dalam Komunikasi Bahasa Arab Santri Pondok Modern Madinah Lampung Timur (Kajian Sosiolinguistik) - Nur Fauziah Fatawi (Institut Agama Islam Negeri Metro, 2018)
This research discusses about the phenomena of blended code in Arabic conversation of students of Madinah Modern Islamic Boarding School. This phenomena happen because a majority of students in saying Arabic are still influenced by local language and less balance in mastering two languages. So that, often happening deviation and appearing language case names mingled code. Related with the gotten blended code data, the researcher uses blended code theory filed by Muysken for analyzing the data. There are three blended cose by Muysken are insertion, alternation, and congruent lexicalization. The method which is used in this research are observation and interview method. First: observation method, this method has base technique. It is a skillful involved free observed technique note, and record. Second: interview method, at interview method applied by inducement technique, this technique is used as base technique and record technique as continuing technique. The objective of this research is to identify mingled code in Arabic conversation of students of Madinah Boarding School, local language elements in Arabic.